Aspects of multigap and multilayer superconductivity - Möckli, David (2017)
This dissertation is composed of two parts. The first part was developed at Universidade Federal Fluminense (UFF) under the supervision of Prof. Dr. Evandro Vidor Lins de Mello and addresses the temperature dependence of the superconducting gaps in ironbased superconductors. The second part was developed at the Eidgenössische Technische Hochschule Zürich (ETH) during a visiting year under the supervision of Prof. Dr. Manfred Sigrist. This part concerns the effect of vortices on the superconducting properties of a three-layer system. The following paragraph is the abstract of part one. The last paragraph is the abstract of part two. The temperature dependence of the multiple superconducting gaps in the typical high-Tc iron-based superconductor Ba0.6K0.4Fe2As2 is studied. These multiband ironbased superconductors display multiple superconducting gaps with different coupling ratios 2Δ0/kBTc, but a single Tc. The guiding question throughout this project is: is it possible to reproduce the various coupling ratios and single Tc observed in Fe-based superconductors within a weak-coupling Bogoliubov-deGennes theory? This dissertation proposes two distinct mechanisms through which it is possible to reproduce the temperature dependence of the multigap structure of Ba0.6K0.4Fe2As2. The first proposal shows how intrinsic charge inhomogeneity might lead to a temperature dependent Cooper pairing potential. The second proposal uses arguments from inhomogeneous superconductivity applied to multiband superconductors to introduce a temperature dependent chemical potential. In part two, we investigate the pair-density wave phase of multilayer superconductors in the context of a Ginzburg-Landau theory. In multilayer systems, due to local inversion symmetry breaking at the outer layers, a Rashba spin-orbit coupling is induced. This combined with a perpendicular Pauli limiting magnetic field stabilizes a pair-density wave (PDW) phase, which is achieved through a first-order phase transition. The PDW phase is robust against magnetic fields. The central issue discussed in this dissertation is whether orbital limiting (on top of dominant paramagnetic limiting) destroys the PDW phase. We find that orbital limiting does not destroy the the PDW phase and investigate the behavior of a single vortex core through the first-order BCS-PDW phase transition. As a subproject, we also study the paramagnetic effect on the reversible magnetization curves of high-κ type II superconductors by generalizing a circular cell method within a Ginzburg-Landau theory.